Questionnaire from the Bureau of Military History on the Rising of Easter Week 1916 and associated events - Bureau of Military History, 1913-1921 (1948)
Two blank copies.
Keywords: Irish Republican Army; Irish Volunteers; Ireland -- History -- 1922-; Ireland -- History -- 1910-1921